Effect of Combined Medical and Surgical Induction of Labour in Term Pregnancy at Rajshahi Medical College Hospital - Lovely, Nur A Atia; Islam, AHM Tohurul; Ali, Obaidullah Ibne; Khatun, Rokeya (TAJ: Journal of Teachers Association, 2019)
This prospective clinical study was conducted in the Department of Obstetrics & Gynaecology in Rajshahi Medical College Hospital from January to December 2007. A total sample of about 100 selected primigravid women were divided into two groups. Group-I was given medical induction by misoprostol orally and Group-II by oral misoprostol followed by artificial rupture of membrane (ARM) for induction of labour. This study specifically evaluated the effect of oral misoprostol and the combined medical & surgical method, on unripe cervix of primigravid women with term pregnancies and has shown that combined method can successfully initiate labour and also lower the rate of caesarean section and significantly lowering the induction delivery time. TAJ 2018; 31(2): 17-20